2018
DOI: 10.1002/mrd.22955
|View full text |Cite
|
Sign up to set email alerts
|

A proinflammatory response of bovine endometrial epithelial cells to active sperm in vitro

Abstract: In the cow, cryopreserved semen is inseminated into the uterus, and most of sperm are removed by backflow and phagocytes. Nevertheless, the mechanism responsible for sperm phagocytosis is unclear. Here, we used cultured bovine uterine epithelial cells (BUECs) to investigate the uterine response to sperm and the mechanism that activates polymorphonuclear neutrophils (PMNs). BUEC monolayers were co-cultured with different numbers of washed sperm obtained from cryopreserved semen (10 , 10 , and 10 sperm/ml) for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 41 publications
2
54
0
2
Order By: Relevance
“…Additionally, work in other species indicates that human and murine sperm express TLR2 and TLR4, although this has not been confirmed in the horse [151]. In bovine, in vitro studies suggested that sperm can stimulate transcription of pro-inflammatory cytokines, including chemokines (TNFα, IL1β, CXCL8) and prostaglandin E and activate the local complement system (C3) mediated via TLR2/4 [152][153][154].…”
Section: Innate Immune Response To Endometritismentioning
confidence: 99%
“…Additionally, work in other species indicates that human and murine sperm express TLR2 and TLR4, although this has not been confirmed in the horse [151]. In bovine, in vitro studies suggested that sperm can stimulate transcription of pro-inflammatory cytokines, including chemokines (TNFα, IL1β, CXCL8) and prostaglandin E and activate the local complement system (C3) mediated via TLR2/4 [152][153][154].…”
Section: Innate Immune Response To Endometritismentioning
confidence: 99%
“…Despite the extensive body of evidence in the mouse, in cattle, the effect of SP on embryo development and survival is not clear. Both sperm and SP have been shown to induce expression of proinflammatory-related genes in the endometrium after infusion of SP into the bovine uterus (Elweza et al, 2018;Ibrahim et al, 2019;Ortiz et al, 2019). However, using a similar infusion technique, no improvement in the fertility of dairy heifers (Odhiambo et al, 2009) or cows (Ortiz et al, 2019) was observed.…”
Section: Introductionmentioning
confidence: 99%
“…These apparent inter-species differences in the role of SP in fertility may be due, in part, to the known variation in composition of this fluid (Rodger, 1976;Druart et al, 2013), owing to differences in accessory gland size, type and level of fluid contribution to the ejaculate (Bedford, 2015). Indeed, caution is needed when interpreting some of the aforementioned bovine studies as some used SP collected by electroejaculation (Ibrahim et al, 2019), others by artificial vagina (Odhiambo et al, 2009) and others do not mention the collection method (Elweza et al, 2018;Ortiz et al, 2019). Collection method significantly influences the composition of SP (Rego et al, 2015) and consequently has a tremendous impact on endometrial response in vitro (Fernandez-Fuertes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperm binding to BOECs promotes a shift to an anti‐inflammatory response by upregulating IL10, TGFB, and PGE2 and downregulates sperm phagocytosis by PMN via PGE2 (Marey et al, ). Thus, the bovine oviduct provides a rich immune tolerant environment to protect sperm from phagocytosis while supporting sperm survival in the oviduct (Elweza et al, ; Marey et al, ).…”
Section: Testicular Immune Mechanismmentioning
confidence: 99%